Investigation of possible neuroprotective effects of some plant extracts on brain in bile duct ligated rats. Issue 8 (26th June 2021) - Ozel, Armagan Begum; Cilingir‐Kaya, Ozlem Tugce; Sener, Goksel; Ozbeyli, Dilek; Sen, Ali; Sacan, Ozlem; Yanardag, Refiye; Yarat, Aysen
Abstract: This study aimed to investigate the possible neuroprotective effects of bitter melon (BM), chard, and parsley extracts on oxidative damage that may occur in the brain of rats with bile duct ligation (BDL)‐induced biliary cirrhosis. It was observed that lipid peroxidation (LPO), sialic acid (SA), and nitric oxide (NO) levels increased; glutathione (GSH) levels, catalase (CAT) activity, and tissue factor (TF) activity decreased significantly in the BDL group. However, in groups with BDL given BM, chard, and parsley extracts LPO, SA, NO levels decreased; GSH levels and CAT activities increased significantly. No significant differences were observed between groups in total protein, glutathione‐S‐transferase, superoxide dismutase, and boron. Histological findings were supported by the biochemical results. BM, chard, and parsley extracts were effective in the regression of oxidant damage caused by cirrhosis in the brain tissues. Practical applications: Bitter melon (BM), chard, and parsley have antioxidant properties due to their bioactive compounds which are involved in scavenging free radicals, suppressing their production, and stimulating the production of endogenous antioxidant compounds. Since BM, chard, and parsley extracts were found to be effective in the regression of oxidant damage caused by cirrhosis in the brain tissues, these plant extracts may be an alternative in the development of different treatment approaches against brain damage in cirrhosis. At the same time, these species have been used as food by the people for many years. Therefore, they can be used safely as neuroprotective agents in treatment. Abstract : The present study investigated the protective effects of bitter melon, chard and parsley extracts on oxidative damage that may occur in brain of rats with bile duct ligation induced biliary cirrhosis. Bitter melon, chard, and parsley extracts were effective in the regression of oxidant damage caused by cirrhosis in the brain tissues. Histological findings were confirmed by the biochemical results.